Impact of implicit vs. explicit Instructions on tactical performance in under-20 soccer players - Abreu, Cristóvão de Oliveira; Aburachid, Layla Maria Campos; Lima, Igor Mendes; Moura, Felipe A.; Bedo, Bruno L. S.; Ribas, Schelyne; Praça, Gibson Moreira (Frontiers in Sports and Active Living, 2024)
Introduction This study aimed to verify whether implicit and explicit informational constraints generate differences in tactical performance and behavior in U-20 national-level soccer players. Methods Thirty-two under-20 male athletes from two clubs participated. Four 4-a-side small-sided games (SSG) protocols were used: R1 - explicit rule for high-press marking, R2 - implicit rule for high-press marking, R3 - game with both previous rules simultaneous and FR - free game, without additional rules. SSGs comprised 4 vs. 4+ goalkeepers games on a 42 m × 29 m field. Position data from 10 Hz Global Positioning System (GPS) devices were used to evaluate individual and collective tactical behavior (spatial occupation metrics) and performance (interpersonal coordination). MANOVA was used for normally distributed variables, and Friedman's with Dunn or Bonferroni post hoc was used for variables without normal distribution. For SEI, an ANOVA was used with Bonferroni post hoc. Results The R1 protocol showed higher SEI, length, width, and LpWratio than the FR protocol (p = 0.009). There was an effect of the different protocols in SEI values (p < 0.001). Under the explicit rule, players also showed the highest in-phase interpersonal coordination values (p < 0.001). Discussion Providing players with explicit tactical instructions improves tactical performance acutely for high-pressing defensive actions.